Effect Burning Temperature and Soaking Time of Pre-treatment hydrochloric acid toward the Characteristic of Ultra-Fine Silica Obtained From rice husk Ash - mohd baba sakri, Muhamad shafiq (IRC, 2014)
Rice husk ash is one of the material that can producing silica (SiO2) and it is one of the important chemical composition Portland cement. The objective of this research to study the effect of soaking time and burning temperature toward physical and chemical characteristic silica obtained from the pre-treatment process. Hydrochloric acid (HCI) with 0.1N concentration was used to remove alkaline impurities on the surface of rice husk ash. Five different soaking time were used which are 1h,2h,3h,4h and 5h. For the burning process, three different temperature were used which are 600°C, 700°C and 800°C. Rice husk ash will be grinded using planetary ball mill (mechanical activation) at maximum of 350rpm for 15 minutes. The sample will be tested using five different machine which are X-ray fluorescence (XRF), scanning electron microscopy (SEM), particle size analysis (PSA), atomic absorption spectroscopy (AAS), and Brunauer– Emmett–Teller test (BET) to study chemical composition, removal particle during soaking time, shape of particle and size of particle. Based the research it shown the 4 h soaking time with burning temperature 600°C temperature produced the highest content of silica which is 97.6%. In the future, the different type of acid and concentration will be used as chemical solution for pre-treatment process.